Effects of bright light therapy for depression during pregnancy: a randomised, double-blind controlled trial. Issue 10 (28th October 2020) - Bais, Babette; Kamperman, Astrid M; Bijma, Hilmar H; Hoogendijk, Witte JG; Souman, Jan L; Knijff, Esther; Lambregtse-van den Berg, Mijke P
Abstract : Objectives: Approximately 11%–13% of pregnant women suffer from depression. Bright light therapy (BLT) is a promising treatment, combining direct availability, sufficient efficacy, low costs and high safety for both mother and child. Here, we examined the effects of BLT on depression during pregnancy. Design: Randomised, double-blind controlled trial. Setting: Primary and secondary care in The Netherlands, from November 2016 to March 2019. Participants: 67 pregnant women (12–32 weeks gestational age) with a DSM-5 diagnosis of depressive disorder (Diagnostic and Statistical Manual of Mental Disorders). Interventions: Participants were randomly allocated to treatment with either BLT (9000 lux, 5000 K) or dim red light therapy (DRLT, 100 lux, 2700 K), which is considered placebo. For 6 weeks, both groups were treated daily at home for 30 min on awakening. Follow-up took place weekly during the intervention, after 6 weeks of therapy, 3 and 10 weeks after treatment and 2 months postpartum. Primary and secondary outcome measures: Depressive symptoms were measured primarily with the Structured Interview Guide for the Hamilton Depression Scale—Seasonal Affective Disorder. Secondary measures were the Hamilton Rating Scale for Depression and the Edinburgh Postnatal Depression Scale. Changes in rating scale scores of these questionnaires over time were analysed using generalised linear mixed models. Results: Median depression scores decreased by 40.6%–53.1% in the BLT group and by 50.9%–66.7% in the DRLT group. We found no statistically significant difference in symptom change scores between BLT and DRLT. Sensitivity and post-hoc analyses did not change our findings. Conclusions: Depressive symptoms of pregnant women with depression improved in both treatment arms. More research is necessary to determine whether these responses represent true treatment effects, non-specific treatment responses, placebo effects or a combination hereof. Trial registration number: NTR5476.